Visual Heritage Study of Vernacular Architecture as an Object of Cultural Advancement in Tanaberu, Bulukumba: Kajian Visual Heritage terhadap Arsitektur Vernakular sebagai Objek Pemajuan Kebudayaan di Tanaberu, Bulukumba - Qayla Raya Rezki Yuniar (Journal of Arts Education and Design, 2026)
Vernacular architecture is a form of collective cultural knowledge born from the relationship between humans, the environment, and local value systems. In Tanaberu, Bontobahari District, Bulukumba Regency, this heritage is embodied in traditional coastal settlement landscapes and the Pinisi boat-building tradition recognized by UNESCO. However, modernization, shifting lifestyles, and the disruption of intergenerational knowledge transmission pose serious threats to its continuity. This study aims to examine the visual heritage quality of vernacular architecture in Tanaberu as an object of cultural advancement through a measured drawing documentation approach and an exploration of coastal community cultural values. A descriptive qualitative method was employed through field research, with data collected via direct observation, in-depth interviews, visual documentation, and building measurement, alongside purposive sampling for object selection. Findings reveal that Tanaberu's vernacular architecture possesses strong visual heritage characteristics, reflected in its stilt-house forms, use of local timber materials, and building orientation adapted to the coastal environment. Beyond physical attributes, traditional buildings also embody social, cultural, and spiritual values that remain alive in community practices. Measured drawing documentation proved effective as a conservation medium, capable of capturing spatial details and cultural values comprehensively. This research affirms the need for a holistic preservation approach encompassing physical conservation, strengthened visual documentation, cultural education, and local community engagement as part of the effort to advance Bulukumba's cultural heritage.